Principle of Accounting Duality in The Context of Optimizing the Passive Manifestation of Value - Trifonov, Trifon (Research Papers, 2007)
Considered in the work is the actual question for establishing of principle and not only of method for accounting duality in the light of the company’s accounting liabilities optimization. Theoretically is advocated the necessity of relative optimization as an addition to the available one for assets. On the basis of the macroeconomic theory for capital structure an improved model for financial income statement is proposed.